HUBUNGAN DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP PADA PASIEN TUBERKULOSIS RESISTAN OBAT - Virgin, Aprilia; Rahmawati, Indah; Yuliani, Massita Dwi (Medical and Health Journal, 2024)
With treatment for Drug Resistant Tuberculosis requiring the consumption of drugs for a long duration, the importance of good support becomes a necessity. Support from family is a very important aspect for individuals who experience Drug Resistant Tuberculosis as the main source of support. Family support is very important in improving the quality of life of patients with drug-resistant tuberculosis. This study identified the relationship between family support and quality of life in patients with drug-resistant tuberculosis. This study is an analytic observational with a cross-sectional design in the target population of patients with RR (Rifampicin Resistant) and MDR (Multi Drug Resistant) TB who are undergoing treatment at Prof. Dr. Margono Soekarjo Hospital and Ajibarang Hospital in 2022-2023. A total of 32 people were selected as respondents using consecutive sampling method. Inclusion criteria were RR and MDR TB patients who sought treatment at Prof. Dr. Margono Soekarjo Hospital and Ajibarang Hospital in 2022-2023 and were willing to become research respondents after signing informed consent. Exclusion criteria included unclear domicile address, patients not in place during data collection, not filling out the questionnaire completely, not cooperating in the implementation of the study and patients with comorbidities such as HIV, DM, hypertension and COPD. Data analysis used Non Parametric test with Spearman method. A total of 65.6% of subjects had high family support, 31.3% had moderate family support and 3.1% of subjects had low family support. A total of 78.1% of subjects had a good quality of life while 21.9% of subjects had a poor quality of life. The results of the data analysis test using Spearman obtained a significance value of p=0.005 with r=0.481 which showed a significant relationship between family support and quality of life in Drug Resistant Tuberculosis patients with a positive correlation direction and moderate correlation strength. It is concluded that family support is related to quality of life in patients with drug-resistant tuberculosis. Keywords: Family support, quality of life, Drug Resistant Tuberculosis